Evolution and ecology of zooplankton communities. Proc. of a symposium on the structure of zooplankton communities held at Darthmouth College - Kerfoot, W. Charles (London, U.K. Univ. Press of New England, 1980)
Paper presented at a symposium at Darmouth College, August 20-25, 1978, sponsored by the American Society of Limnology and Oceanography
Keywords: Zooplankton--Ecology--Congresses.; Zooplankton--Evolution--Congresses.